Activation of ubiquitin ligase SCF(Skp2) by Cks1: insights from hydrogen exchange mass spectrometry. - Yao, Z; Zhou, M; Kelly, SE; Seeliger, M; Robinson, C; Itzhaki, L (2006)
Skp2 is the substrate recognition subunit of the multi-subunit ubiquitin ligase SCF(Skp2). It consists of an N-terminal F-box domain that binds to the Skp1 subunit and thereby tethers it to the SCF catalytic core, and an elongated C-terminal domain comprising ten Leucine-rich repeats (LRR) that binds the substrate. A small accessory protein, Cks1, is required for SCF(Skp2) to target certain substrates, including the Cyclin-dependent kinase inhibitor p27. Here we have used hydrogen/deuterium exchange monitored by mass spectrometry to investigate the mode of action of Cks1 on SCF(Skp2). We show that complex formation between Cks1 and Skp2 causes conformational changes in both proteins in regions distant from the respective binding sites. We find that Skp2 interacts with a localised region of Cks1 but the interaction causes a global change in the hydrogen exchange behaviour of Cks1. Also, whilst Cks1 binds to the most C-terminal LRRs of the elongated Skp2 molecule, the interaction induces conformational changes at the distant N-terminal LRRs, close to the F-box motif. Further, binding of Cks1 to Skp2 significantly stabilises the interaction between Skp2 and Skp1. The results reveal that the C-terminal substrate recognition region of Skp2 is coupled to the N-terminal Skp1-binding region and thereby to the SCF catalytic core; this result adds to the model proposed previously that, whilst the principal function of the F-box protein is to recruit the substrate, an additional function may be to help position the substrate in an optimal way within the SCF complex to enable efficient ubiquitin transfer.